Dispositivo e contradispositivo na construção poética do retrato - Happke, Rafael (2015)
This paper aims to make an investigation into the use of devices as the camera and counter-devices created specifically for photographic portraits as poetic realizations, seeking a new construction of the appearances represented in them, in an attempt to attain a renewed aesthetic of this photographic category, which has been widely requested since the beginning of photography. This study is based on the works of different artists such as Julia Margaret Cameron, Felix Nadar, Arthur Omar and Sarah Moon, among others, through an observation of the expressions of the portrait that can clarify and ensure a personal poetic achievement that will enrich this subject in the Visual Arts. Secondly, the counter-device plays a key role in the practical and reflective direction of this research. Thus, we seek to analyze the counter-device as a key element and to explore what knowledge it may hold and what action it has in making photography. In this context where devices allow the creation of sensitive objects fitting for reflection, we base our work in Giorgio Agamben, Flusser, Arlindo Machado, Annatereza Fabris and Françoise Soulages among others, and divergent concepts arise throughout the work and problematize the object of this investigation. Finally, we present a series of portraits made during the research that combine theoretical thinking with practice.